I wonder, I wonder. - Frey, Marguerite Kurth (Saint Louis, Concordia Pub. House, 1967)
The father of newborn twins tells his six-year-old and eight-year-old the facts of life from a Christian viewpoint.
Keywords: Sex instruction for children